Commentary (Research Highlights) - D. Skaper, Stephen (CNS & Neurological Disorders - Drug Targets, 2011)
Putting a Finger on Neurotrophic Protein Therapy in Parkinson's Disease Parkinson's disease (PD) was first described in the essay entitled “An Essay of the Shaking Palsy” by James Parkinson in 1817. PD is the most common neurodegenerative movement disorder, whose neuropathological hallmarks are characterized by progressive and profound loss of neuromelanin-containing dopaminergic neurons in the substantia nigra pars compacta with the presence of eosinophilic intracytoplasmic, proteinaceous inclusions termed Lewy bodies and dystrophic Lewy neurites in surviving neurons. Although neuronal cell loss in the substantia nigra pars compacta is pronounced, there is widespread neurodegeneration in the CNS with the pars compacta being involved in midstages of the disease. Clinical manifestations of this complex disease include motor impairments involving resting tremor, bradykinesia, postural instability, gait difficulty and rigidity, along with non-motoric symptoms like autonomic, cognitive, and psychiatric problems. As with many multifactorial diseases, the incidence of PD increases with age. Because of an aging population, improved diagnosis, and prolonged survival, especially in developing countries, the number of patients suffering from PD is predicted to double by the year 2030. The power of neurotrophic factors to regulate neuronal cell survival in the developing nervous system and to promote also survival after injury or protect neurons in toxin-mediated disease models in animals has encouraged the idea that such proteins could be harnessed for the treatment of neurodegenerative disease. In the case of dopaminergic neurons, glial cell line-derived neurotrophic factor (GDNF), a member of the basic fibroblast growth factor superfamily, given intracerebrally has neuroprotective and neurorestorative effects in neurotoxin-induced rodent and non-human primate models of PD. In spite of extensive positive preclinical data and encouraging results from phase I clinical trials, results from phase II studies have been disappointing. Indeed, neurotrophic factor treatment of CNS diseases presents an especially complex problem, since these polypeptides have poor pharmacokinetics and bioavailability and are not able to cross the blood-brain barrier. At the same time, excessive levels of a neurotrophic protein may provoke deleterious side-effects, as evidenced by toxicity (including multifocal cerebellar Purkinje cell loss) observed in rhesus monkeys that received intraputamenal infusion of high concentrations of GDNF. A novel approach to this problem has recently been reported by Laganiere and colleagues, who explored the possibility of engineering zinc finger protein transcription factors (ZFP TFs) that activate the expression of the endogenous GDNF gene. Transcription factors based on Cys2-His2 ZFPs can be engineered to specifically target virtually any gene. By targeting the endogenous gene and exploiting the native promoter, which imposes a physiological upper limit on the level of gene expression from each allele, a ZPF can produce sufficient, but not supraphysiological levels of the therapeutic protein needed to achieve both long-term efficacy and safety. Laganiere et al. designed a human GDNF ZFP TF (hGDNF-ZFP) that recognized a site that is fully conserved between human and rhesus macaque. Having confirmed that hGDNF-ZFP activated rhesus GDNF in rhesus macaque cell lines, the authors then designed and assembled a panel of ZFP activators specific to the rat GDNF promoter. Using an adeno-associated viral vector serotype 2 as the delivery vehicle, the engineered transcription factor that gave the highest levels of rat GDNF activation was tested in the rat 6-hydroxydopamine model of PD. Vector was infused bilaterally into the striatum by convection-enhanced delivery. The modest (∼60%) overall increase in striatal GDNF levels provoked by the ZFP was sufficient to provide marked improvement in all behavioral tests performed. Moreover, functional neuroprotection by the GDNF activator was supported by immunohistochemical demonstration of preservation of tyrosine hydroxylase-positive nigrostriatal neurons. While activation of endogenous GDNF was adequate to protect again neurotoxin lesion in rat, demonstration of efficacy and safety in a nonhuman primate model of PD will be a prerequisite before advancing the ZFP-based approach to the clinic. The dual species-specific GDNF activator should facilitate such studies. In addition, convection-enhanced delivery is expected to provide a more complete coverage of the putamen, unlike previously used infusion protocols. Engineered ZFP activators that drive specific activation of endogenous GDNF combined with highly efficient convection-enhanced delivery may well offer hope to realize the therapeutic potential of GDNF.